Pengaruh Motivasi, Disiplin Kerja, dan Kepuasan Kerja terhadap Kinerja Pegawai Direktorat Perbenihan Tanaman Pangan, Kementerian Pertanian Jakarta - Erlinda Esti Hairunnisa; Syarif Ali (Owner : Riset dan Jurnal Akuntansi, 2022)
ABSTRACT The purpose of this quantitative study is to determine the influence or impact of employee motivation, work discipline, and job satisfaction on employee performance. The topic of this research is a worker at the Ministry of Agriculture's Directorate of Food Crop Germination in Jakarta. In this study, data was collected by sending 58 employees using Google Form questionnaires in the form of questions. For sampling, the saturated sample technique was used. The SmartPLS 3.0 application was utilized to conduct the analysis for this investigation. And the findings show that: 1) employee motivation has a significant impact on employee performance, 2) work discipline has a significant impact on employee performance, 3) job satisfaction has a significant impact on employee performance, and 4) employee motivation, work discipline, and job satisfaction all have an impact on employee performance.